A hybrid system using direct contact membrane distillation for water production to harvest waste heat from the proton exchange membrane fuel cell. (15th March 2018) - Lai, Xiaotian; Long, Rui; Liu, Zhichun; Liu, Wei
Abstract: In this paper, a hybrid system consisting of PEMFC (proton exchange membrane fuel cell) and DCMD (direct contact membrane distillation) was proposed to recover the waste heat from PEMFC for brine water desalination. Parameters determining the performance of this hybrid system were systematically investigated. Results indicate that there exist optimal PEMFC current density and DCMD fresh water inlet mass flow rate, respectively, leading to the maximum energy gain from the fuel chemical energy. In order to analyze the optimal performance of the proposed hybrid system, with the maximum energy gain as the objective function, genetic algorithm method was employed to obtain the optimal PEMFC current density and DCMD fresh solution inlet mass flow rate, thereby, the performance specifications of the hybrid system under different operating temperatures of the PEMFC subsystem. Compared with the single PEMFC system, as operating temperature varies from 328.15 K to 348.15 K, the energy utilization degree can be increased by 201%–266%. Highlights: A novel hybrid system combining electricity generation and fresh water production is presented. This system consists of a PEMFC and a DCMD subsystems. Parameters' impacts on performance of the hybrid system have been analyzed. The maximum energy gain of the hybrid system is investigated based on genetic algorithm. The energy utilization degree of the hybrid system is improved by 266% at 348.15 K.